Zasada ekstensjonalności lokalnej i globalnej - Wójtowicz, Anna (Filozofia Nauki, 2005)
In this article the notions of local and global extensionality principle are defined; the problem of relations between extensionality of a language and theory of extension of a name and extension of a sentence is discussed.